mHealth and Application Technology Supporting Clinical Trials: Today’s Limitations and Future Perspective of smartRCTs - Vogel, Marco M. E.; Combs, Stephanie E.; Kessel, Kerstin A. (Frontiers in Oncology, 2017)
Nowadays, applications (apps) for smartphones and tablets have become indispensable especially for young generations. The estimated number of mobile devices will exceed 2.16 billion in 2016. Over 2.2 million apps are available in the Google Play store® and about 1.8 million apps in the Apple App Store®. Google and Apple distribute nearly 70,000 apps each in the category Health and Fitness, and about 33,000 and 46,000 each in medical apps. It seems like the willingness to use mHealth apps is high and the intention to share data for health research is existing. This leads to one conclusion: The time for app-accompanied clinical trials (smartRCTs) has come. In this perspective article, we would like to point out the stones put in the way while trying to implement apps in clinical research. Further, we try to offer a glimpse of what the future of smartRCT research may hold.